Application of Raman spectroscopy to industrial research: Determination of impurities in glass bottles - Moraes, Samira N. S. [UNESP]; Morgado, Daniella L. [UNESP]; Nalin, Marcelo [UNESP] (Elsevier B.V., 2019)
In the glass industry, impurities occur commonly, however it is fundamental the study of the their nature, because they can generate cracks, bubbles and influence on the colour of the bottles, In order to identify these defects, this work investigates how different impurities in glass bottles can be qualitatively detected using Raman spectroscopy in a specific study of a case. The results obtained by Raman spectroscopy revealed a diversity of crystalline impurities, such as refractories which were first compared to a database made using the raw materials, refractories, and insulating materials provided by the company. Such identification allowed to identify the sources of impurities in the industry, and such information was used to minimize losses during the manufacturing process. These detected impurities came from the oxidation of iron, leading to the formation of crystalline hematite phase; the presence of unmelted refractories in the vitreous composition; or due to the presence of unmelted raw material (silica). As the bubbles and impurities come from different compounds, Raman spectroscopy was a very sensitive technique to determine the probable source of problem.
Keywords: Glass; Bubbles; Impurities; Raman spectroscopy